2018
DOI: 10.4314/ahs.v18i4.40
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic prescriptions and use in under-five children in Ibadan, SouthWestern Nigeria

Abstract: BackgroundIrrational antibiotic prescriptions for children is a global concern requiring periodic evaluation and monitoring.ObjectivesTo assess appropriateness of antibiotic prescribing for under-five children, as well as evaluating mothers' usage of antibiotics for their under-five and reason(s) for use.MethodCross-sectional review of out-patient case-notes of under-five using principles of antibiotic prescribing and a questionnaire-guided interaction with under-five mothers.ResultsNearly all (445;98.9%) anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
5
15
0
1
Order By: Relevance
“…The studies in the following countries also found antibiotic prescribing to be high; in India by Majhi The most common antibiotic class that were prescribed were penicillins followed by cephalosporins. This is even though most bacteria are resistant against penicillins [36]. These findings are in agreement with what was found in studies that were done in Ethiopia, Cameroon, Nigeria, and Iraq [24,29,36,37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The studies in the following countries also found antibiotic prescribing to be high; in India by Majhi The most common antibiotic class that were prescribed were penicillins followed by cephalosporins. This is even though most bacteria are resistant against penicillins [36]. These findings are in agreement with what was found in studies that were done in Ethiopia, Cameroon, Nigeria, and Iraq [24,29,36,37].…”
Section: Discussionsupporting
confidence: 91%
“…This is even though most bacteria are resistant against penicillins [36]. These findings are in agreement with what was found in studies that were done in Ethiopia, Cameroon, Nigeria, and Iraq [24,29,36,37]. These similarities in the findings could be due to the availability of these drugs in these various hospitals and hence their use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the inadequate enforcement of regulation of access to antibacterials especially in the private sector coupled with nonfunctional microbiology laboratories in most health facilities could be responsible for the high antibacterial use in children with symptoms of ARIs observed in this study. The high antibacterial resistance selection pressure created by high antibacterial use is a potential driver of resistance emergence and spread (20), further diminishing the already limited choices of antibacterial therapy for infectious diseases especially in LMICs (10). The high prevalence of antibacterial use reported in this study is similar to reports of previous studies done in LMICs [3,[7][8][9][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 79%
“…Muchas de las prescripciones de antibióticos se realizan en forma empírica, superando en diversos estudios un 50% de los casos [17,18] . Adicionalmente, se debe considerar que cerca de una tercera parte a la mitad de las prescripciones de antibióticos son por infecciones del tracto respiratorio; y siendo la mayor parte de estas infecciones de origen viral, está demostrado que los antibióticos no afectan la duración, los síntomas y la intensidad de la enfermedad.…”
Section: Antibióticos En La Práctica Diariaunclassified